Drug-Coated versus Conventional Balloons to Improve Recanalization of a Coronary Chronic Total Occlusion after Failed Attempt: The Improved-CTO Registry - Ignacio J. Amat-Santos; Giorgio Marengo; Luiz F. Ybarra; Jose Antonio Fernández-Diaz; Ander Regueiro; Alejandro Gutiérrez; Javier Martín-Moreiras; Juan Pablo Sánchez-Luna; Jose Carlos González-Gutiérrez; Clara Fernandez-Cordon; Manuel Carrasco-Moraleja; Stéphane Rinfret (Journal of Interventional Cardiology)
Background. Chronic total occlusion (CTO) plaque modification (CTO-PM) is often used for unsuccessful CTO interventions. Methods. A multicenter, prospective study included consecutive patients with failed CTO recanalization. At the end of the failed procedure, patients received either a conventional (CB) or drug-coated balloon (DCB) for CTO-PM at the operator’s discretion and underwent a new attempt of CTO recanalization ∼3 months later. Results. A total of 55 patients were enrolled (DCB: 22; CB: 33), with a median age of 66 years. The median J-score was 3, and CCS angina classes III–IV were present in 45% of the patients. After the first CTO-PCI attempt, no in-hospital cardiac deaths were registered. The overall rate of in-hospital myocardial infarction was 3.6%, without significant differences between the DCB and CB groups (4.5% after DCB vs 3.0% after CB, p=0.999). The success rate of the second CTO-PCI attempt was 86.8%, with a periprocedural complication rate of 5.7% and with an overall rate of in-hospital complications of 24.5%, without significant differences between the 2 groups (13.6% in the DCB group vs 32.2% in the CB group, p=0.195). Compared with CB, in the DCB group, the second CTO-PCI required a shorter median fluoroscopy time (33 vs 60 min, p<0.001), a lower contrast volume (170 vs 321 cc, p<0.001), and a lower radiation dose (1.7 vs 3.3 Gy, p<0.001). At 1-year follow-up, outcomes were comparable between the 2 strategies, target vessel failure occurred in 5.7% and major adverse cardiovascular events in 18.2% (13.6% in the DCB group vs 21.2% in the CB group, p=0.494). Conclusions. PM after CTO recanalization failure is safe and warrants high success rates when a second attempt is performed. A DCB strategy for CTO-PM does not seem to ensure higher success or better clinical outcomes, but its use was associated with simpler staged procedures. This trial is registered with NCT05158686.